Long-term air pollution exposure and gait speed decline among older Adults: A longitudinal analysis - Boeun Kim; Anjum Hajat; Amanda J. Gassett; Claire E. Adam; Joel D. Kaufman; Erin O. Semmens; Cindy S. Leary; Annette L. Fitzpatrick (Environmental Research, 2026)

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Use of antihypertensive medications and breast cancer risk - Babette S. Saltzman; Noel S. Weiss; Weiva Sieh; Annette L. Fitzpatrick; Anne McTiernan; Janet R. Daling; Christopher I. Li (Cancer Causes & Control, 2013)

Effects of injected methylmercury on the hatching of common loon (Gavia immer) eggs - Kevin P. Kenow; Michael W. Meyer; Ronald Rossmann; Annette Gendron-Fitzpatrick; Brian R. Gray (Ecotoxicology, 2011)

C-reactive protein, interleukin-6, and prostate cancer risk in men aged 65 years and older - Brandon L. Pierce; Mary L. Biggs; Marvalyn DeCambre; Alexander P. Reiner; Christopher Li; Annette Fitzpatrick; Christopher S. Carlson; Janet L. Stanford; Melissa A. Austin (Cancer Causes & Control, 2009)

Genetic Susceptibility to Prostate Cancer: Prostate-specific Antigen and its Interaction with the Androgen Receptor (United States) - Weiva Sieh; Karen L. Edwards; Annette L. Fitzpatrick; Sengkeo L. Srinouanprachanh; Fred M. Farin; Stephanie A. Monks; Richard A. Kronmal; David L. Eaton (Cancer Causes & Control, 2006)